Contribution of oral triamcinolone to treating proliferative and necrotising otitis externa in a 14-year-old Persian cat. Issue 1 (February 2017) - Momota, Yutaka; Yasuda, Junya; Arai, Nobuaki; Yamamoto, Masami; Yoshimura, Hisashi; Ikezawa, Mitsutaka; Suzuki, Shuji; Takahashi, Kimimasa; Sako, Toshinori
Case summary: A 14-year-old female spayed cat was referred for recurrent otitis externa and unusual proliferative lesions in both ear canals. The affected pinnae and external ear canals were covered with large reddish-to-dark-brown verrucous and necrotic tissue. Friable material and exudates occluded both ear canals. Proliferative lesions developed in both ears 2–3 weeks before referral. The histopathological diagnosis from two biopsies obtained from the friable materials with endoscopic biopsy forceps was proliferative and necrotising otitis externa (PNOE). Treatment was initiated with once-daily application of a potent topical glucocorticoid (mometasone furoate) to both ears. Although the auricle and vertical ear canals responded well, no improvement was seen in the horizontal part of the ear canal after 9 weeks. Therefore, oral triamcinolone (0.9 mg/kg q24h) was added for 1 week, and was then tapered (q48h) for 3 weeks. Most lesions resolved, and after a further 2 weeks of prednisolone (2 mg/kg q48h) there was complete resolution. No recurrence was observed during a 2 year follow-up period. Relevance and novel information: PNOE commonly occurs in kittens, but it can develop in older cats. To our knowledge, the PNOE in this case is the oldest age of onset reported. This condition is rare and was only described recently, and therapeutic options appear limited. According to previously published reports, steroid therapy is ineffective, and tacrolimus is the only treatment known to achieve resolution. However, oral and topical glucocorticoids were beneficial in this case.